(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the reasons for the low achievement in mathematics among primary school students from the point of view of male and female teachers. A questionnaire was prepared to measure the low level and achievement of students in mathematics. The procedures and study were applied to a sample of 200 individuals. Male and female teachers represent 80% of the original population for this study, and they are identified by mathematics teachers at the primary level affiliated with the General Directorate of Karkh Education/Third. After analyzing the data and processing it statistically, the results of the study were surveyed and the results were as follows: Lack of parental attention leads to...low student achievement at the primary level The lack of modern equipment and methods leads to a decline in student achievement. Behavioral problems affect students’ achievement performance in mathematics.